Comparative Photocatalytic Activity and Total Organic Carbon Removal Efficiency of TiO2 And ZnO for Reactive Black 5 Photodegradation - Ozkan, Betuel Cicek; Selen, Veyis; Guelyuez, Feyza; Dursun, Guelbeyi (Wiley-V C H Verlag Gmbh, 2023)
The photocatalytic performance of TiO2 and ZnO was comparatively studied for photocatalytic degradation of reactive black 5 (RB5) under artificial UVC irradiation. The effect of initial solution pH, catalyst concentration, initial RB5 concentration, purging oxygen rate, stirring rate, and process temperature on the degradation process by TiO2 and ZnO was investigated. In addition, total organic carbon (TOC) analysis has been employed for each parameter to detect the presence of organic intermediates and the photodegradation performance of catalysts simultaneously with the photocatalytic degradation process. The RB5 photodegradation was more rapid in the aqueous medium by TiO2 under UVC irradiation compared to the catalysis by ZnO. On the other hand, the slower photocatalysis by ZnO resulted in generating more organic intermediates. The structural and morphological analyses of photocatalysts TiO2 and ZnO were performed using XRD and FE-SEM techniques. The UV-vis spectroscopy measurements supported that the TiO2 demonstrated evidently better photocatalytic activity than ZnO for RB5 degradation.
Keywords: Photocatalytic activity; reactive black 5; titanium dioxide; total organic carbon; zinc oxide